A small-scale experimental prototype for exhaust heat-based mechanical energy harvesting in passenger vehicles, with extrapolation to heavy vehicles - Muhammad Bader Munir; Muhammad Waheed Ashraf; Najam ul Qadir; Sibghat Ullah; Allah Ditta (Next Research, 2026)

Expression Analysis and Protein Modeling of Small Heat Shock Protein 20 VIS1 Gene in Six Solanum lycopersicum Determinate Varieties - Zubair Ahmad; Zaigham Abbas; Mirza Zian Ul Abideen; Shahzad Hussain Shah; Ahmad Ali; Zahid Ullah; Javed Iqbal; Rashid Iqbal; Allah Ditta; Mohamed Taha Yassin (Plant Molecular Biology Reporter, 2026)

Optimizing Nitrogen Fertilization through Combined Sources and Split Humic Acid Application Improves Wheat Productivity and Stress Resilience in Semi-arid Soils - Tahir Fazal; Muhammad Aurangzaib; Umar Arshad; Rashid Iqbal; Muhammad Raheel; Allah Ditta; Mohamed Taha Yassin (Water, Air, & Soil Pollution, 2026)

Green-Synthesized Zinc Oxide Nanoparticles from Selenicereus grandiflorus Exhibit Potent Nematicidal Activity Against Meloidogyne incognita - Sidra Ahmad; Mian Afaq Ahmad; Nayab Ahmad; Fazal Umer; Iqbal Munir; Md. Shahinoor Islam; Gulzar Ahmad; Muhammad Ijaz; Allah Ditta; Rashid Iqbal; Badr Aldahmash; Ahmed Rady (Current Microbiology, 2026)

Integrative screening of cotton genotypes against salt stress using pre-breeding and machine learning methods - Zunaira Anwar; Sajid Shokat; Allah Ditta; Muhammad Kashif Riaz Khan (Biocatalysis and Agricultural Biotechnology, 2026)

Spatio-temporal analysis of land surface temperature, urban heat island intensity, and urban thermal field variance index in Faisalabad, Pakistan - Muhammad Naveed; Bilal Hussain; Awais Ali; Ayesha Mariam; Abdul Ghafoor; Fozia Allah Ditta; Basharat Ali (Air Quality, Atmosphere & Health, 2026)

Correction: Soil C/P Stoichiometry Mediated Microbially Driven Phosphorus Mobilization: New Insight in Soil P Management - Khuram Shehzad Khan; Muhammad Naveed; Allah Ditta; Tajwar Alam; Muhammad Zahid Mumtaz; Aown Abbas; Lingling Li (Journal of Soil Science and Plant Nutrition, 2026)

Analyzing the Food-Energy Nexus of Irrigated Crops in Pakistan: Implications for Food Security and Agricultural Sustainability - Sadia Allah Ditta; Asmat Ullah; Rasool Bux Mahar; Kamran Ansari; Tayyaba Suhail; Waqas Ahmed (Agricultural Research, 2026)

Sublethal effects of azadirachtin on life table parameters of Musca domestica (Diptera: Muscidae): implications for population dynamics in Pakistan - Naeem Iqbal; Nauman Sadiq; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Muhammad Nadir Naqqash; Adnan Akhter (International Journal of Tropical Insect Science, 2026)

Ethnoecology of the Wakhi community in Broghil Valley, Chitral, Pakistan - Hasin Sahar; Lal Badshah; Muhammad Abdul Aziz; Allah Ditta (Genetic Resources and Crop Evolution, 2026)

Integrating Google Earth Engine and machine learning for urban land use and land cover dynamics analysis - Mubarak Ahmad; Khan Alam; Maqbool Ahmad; Komal Khan; Bahadar Zeb; Allah Ditta (Environmental Monitoring and Assessment, 2026)

Heat-induced modulation of growth parameters and gene expression profiles in maize (Zea mays L.) seedlings - Iqbal Hussain; Tadashi Sato; Badr Alharthi; Abdul Wahid; Allah Ditta; Zunaira Anwar; Aqsa Ijaz; Rashid Iqbal; Sajid Fiaz (Molecular Biology Reports, 2025)

PM2.5 pollution and its correlation with meteorological parameters over the four capital cities of Pakistan - Bahadar Zeb; Jawad Nasir; Khan Alam; Allah Ditta; Muhammad Arif Aman; Muhammad Shafiq (Environmental Monitoring and Assessment, 2025)

Risk assessment of synthetic insecticides and botanicals to Western honey bee, Apis mellifera (Hymenoptera: Apidae) - Sami Ullah; Naeem Iqbal; Muhammad Sohail Shahzad; Hafiz Azhar Ali Khan; Khalid Rafiq; Allah Ditta Abid; Mudssar Ali; Shafqat Saeed (International Journal of Tropical Insect Science, 2025)

Heavy metals contamination in water, soil, and potatoes in Sargodha and Sillanwali, Pakistan, with human health implications - Kafeel Ahmad; Mutiya Zafar; Zafar Iqbal Khan; Asma Ashfaq; Muhammad Mazhar Iqbal; Tayyaba Naz; Allah Ditta; Mashal Maqsood; Shahzad Akhtar; Ijaz Rasool Noorka (Environmental Monitoring and Assessment, 2025)

Soil C/P Stoichiometry Mediated Microbially Driven Phosphorus Mobilization: New Insight in Soil P Management - Khuram Shehzad Khan; Muhammad Naveed; Allah Ditta; Tajwar Alam; Muhammad Zahid Mumtaz; Aown Abbas; Lingling Li (Journal of Soil Science and Plant Nutrition, 2025)

Large increase in anthropogenic emissions in an urban environment and their associated air quality implications - Mubarak Ahmad; Maqbool Ahmad; Khan Alam; Bahadar Zeb; Komal Khan; Allah Ditta (Environmental Monitoring and Assessment, 2025)

Nutritional and phytochemical potential of Diospyros Kaki L. fruit from the foothills of hindukush ranges, district dir upper, Khyber Pakhtunkhwa, Pakistan - Waqar Ahmad; Khan Sher; Allah Ditta; Hussain Shah; Shabir Ahmad; Mohamed El-Zaidy; Manal Abdulaziz Binobead; Rashid Iqbal; Sirojidinov Bekhzod; Uralov Abdumannon; Khujanov Alisher; Kurbaniyazov Bakbergen; et al. (Genetic Resources and Crop Evolution, 2025)

Adsorptive removal of Congo red dye from industrial effluent using cotton calyx iron oxide (CC-Fe3O4) composite - Shoomaila Latif; Amna Zahid; Fozia Batool; Samia Kanwal; Allah Ditta (Environmental Monitoring and Assessment, 2025)

Evaluation of genetic diversity and population structure of the Chinese chestnut (Castanea mollissima) by using NR-SSR markers - Saman Zulfiqar; Muhammad Mahran Aslam; Allah Ditta; Rashid Iqbal; Abd El-Zaher M. A. Mustafa; Mohamed S. Elshikh; Muhammad Uzair; Saltanat Aghayeva; Muhammad Qasim; Sezai Ercisli; Ozhan Simsek; Tolga Izgu; et al. (Genetic Resources and Crop Evolution, 2025)

Nanoparticles in plant resistance against bacterial pathogens: current status and future prospects - Maria Gul; Raham Sher Khan; Zia Ul Islam; Sumayya Khan; Amina Shumaila; Sidra Umar; Sajad Khan; Brekhna; Muhammad Zahoor; Allah Ditta (Molecular Biology Reports, 2024)

Toxicity of different nitrogenous fertilizers on Aedes aegypti larvae (Linnaeus) (Diptera: Culicidae) - Sikander Ali; Unsar Naeem-Ullah; Naeem Iqbal; Hafiz Azhar Ali Khan; Allah Ditta Abid; Muhammad Sohail Shahzad; Shafqat Saeed; Muhammad Usman; Muhammad Nadir Naqqash (International Journal of Tropical Insect Science, 2024)

Physicochemical properties and performance of non-woody derived biochars for the sustainable removal of aquatic pollutants: A systematic review - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Rashid Iqbal; Faisal Zulfiqar; Akash Tariq; Allah Ditta (Chemosphere, 2024)

Guar gum, Ulva lactuca L. biomass, and xanthan gum-based copolymer novel biosorbent for adsorptive removal of acid orange 10 - Samia Kanwal; Fozia Batool; Gulnaz Sharif; Hafiza Komal Naeem; Sobia Noreen; Humaira Yasmeen Gondal; Umar Bin Kamal; Allah Ditta (Biocatalysis and Agricultural Biotechnology, 2024)

Zinc and amino acids improve the growth, physiological, and biochemical attributes of corn under different irrigation levels - Ayman M.S. Elshamly; Rashid Iqbal; Baber Ali; Iftikhar Ahmed; Muhammad Irfan Akram; Shehzad Ali; Allah Ditta; Fatih ÇIĞ; Mohamed S. Elshikh; Abd El-Zaher M.A. Mustafa; Mahdy H. Hamed (Rhizosphere, 2024)

An analysis of lncRNAs related to fiber quality and the discovery of their target genes in a Gossypium hirsutum line with Gossypium mustelinum introgression - Baohua Wang; Meijun Ji; Hui Fang; Haijing Gu; Teame Gereziher Mehari; Jinlei Han; Wenxiang Feng; Xuehan Huo; Jingxia Zhang; Yu Chen; Jun Zhang; Allah Ditta; et al. (Theoretical and Applied Genetics, 2024)

Green synthesized silver nanoparticles: Characterization, phytostimulatory impacts, and degradation potential for organic pollutants - Ghania Abbas; Fozia Batool; Ambreen Ahmed; Shabana Wagi; Humaira Yasmeen Gondal; Farah Maqsood; Ehab A. Abdelrahman; Hafiza Komal Naeem; Samia Kanwal; Muhammad Mustaqeem; Allah Ditta (Biocatalysis and Agricultural Biotechnology, 2024)

Climate change variables modify microbial community structure and soil enzymes involved in nitrogen and phosphorus metabolism - Muhammad Bashir Ahmed Siddique; Azeem Khalid; Allah Ditta; Shahid Mahmood; Abed Alataway; Ahmed Z. Dewidar; Mohamed A. Mattar (Rhizosphere, 2023)

Variation in Soil C and P Fractions Associated with Microbial Biomass - Khuram Shehzad Khan; Muhammad Naveed; Muhammad Farhan Qadir; Adeel Ahmad; Hafiz Hassan Javed; Allah Ditta (Journal of Soil Science and Plant Nutrition, 2023)

Sources, impacts, factors affecting Cr uptake in plants, and mechanisms behind phytoremediation of Cr-contaminated soils - Sadeeq Ullah; Qingling Liu; Shiyong Wang; Amin Ullah Jan; Hafiz M. Adeel Sharif; Allah Ditta; Gang Wang; Hefa Cheng (Science of The Total Environment, 2023)

Genome-wide analysis of the LAZ1 gene family in Gossypium hirsutum - Tingting Deng; Zongjin Pan; Wei Wang; Yingying Tang; Wenxiang Feng; Dequan Li; Kangtai Sun; Allah Ditta; Muhammad K.R. Khan; Yunying Cao; Baohua Wang (Molecular Biology Reports, 2023)

Adsorption potential of orange rind–based nanosorbents for the removal of cadmium(II) and chromium(VI) from contaminated water - Samia Kanwal; Hafiza Komal Naeem; Fozia Batool; Awais Mirza; Ehab A. Abdelrahman; Gulnaz Sharif; Farah Maqsood; Muhammad Mustaqeem; Allah Ditta (Environmental Science and Pollution Research, 2023)

Correction: KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)

A systematic review on the bioremediation of metal contaminated soils using biochar and slag: current status and future outlook - Sajid Mehmood; Waqas Ahmed; Juha M. Alatalo; Mohsin Mahmood; Rana Muhammad Ammar Asghar; Muhammad Imtiaz; Naseer Ullah; Wei-dong Li; Allah Ditta (Environmental Monitoring and Assessment, 2023)

KASP mapping of QTLs for yield components using a RIL population in Basmati rice (Oryza sativa L.) - Hamza Ashfaq; Reena Rani; Naila Perveen; Allah Ditta Babar; Umer Maqsood; Muhammad Asif; Katherine A. Steele; Muhammad Arif (Euphytica, 2023)
Super Basmati is an elite variety with extra-long grains and superior quality but its yield is severely affected by water stress. Recombinant inbred lines (RILs) developed from the cross of Super Basmati and IR55419-04 (a coarse grained variety with high yield potential) were used to identify and map yield-related quantitative trait loci (QTLs) under normal field conditions. Genotypes for 244 KASP markers were obtained from 188 F 9 RILs and a linkage map constructed of 1369.4 cM, with average marker interval of 10.5 cM. Eleven agronomic traits were phenotyped in RILs and parents. Composite interval mapping and inclusive composite interval mapping model identified 21 common QTLs related to nine agronomic traits; of the QTLs identified, twelve mapped at novel positions. LOD scores ranged from 2.51 for number of filled grains ( qFG1.1 ) to 16.8 for plant height ( qPH1.1 ). Four major effect QTLs could explain 20% of variation related for plant height, hundred-grain weight and grain width. Alleles from IR55419-04 improved grain filling, grain weight and grain width, while alleles from Super Basmati contributed to longer grains, panicles and flag leaves. Putative candidate genes were identified for 18 yield-related QTLs. These results validate the use of KASP genotyping for QTL mapping of yield-related traits in a bi-parental segregating population. SNPs in the QTLs identified in this study can be used in marker assisted selection for yield components to improve Basmati rice.

Optimal root oxygen release from two macrophytes Saururus cernuus L. and Pistia stratiotes L. varies with light and temperature in simulated constructed wetlands microcosms - Faiza Rehman; Ahmed Usman; Allah Ditta; Fahd S. Khan; Qaisar Mahmood; Abed Alataway; Ahmed Z. Dewidar; Mohamed A. Mattar (Rhizosphere, 2023)

Genome-wide identification and expression analysis of terpene synthases in Gossypium species in response to gossypol biosynthesis - Teame Gereziher Mehari; Hui Fang; Wenxiang Feng; Yuanyuan Zhang; Muhammad Jawad Umer; Jinlei Han; Allah Ditta; Muhammad K. R. Khan; Fang Liu; Kai Wang; Baohua Wang (Functional & Integrative Genomics, 2023)

Examining groundwater sustainability through influential floods in the Indus Plain, Pakistan - Arshad Ashraf; Mussarat Jabeen; Sadia Allah Ditta; Zulfiqar Ahmad (Sustainable Water Resources Management, 2023)

Remediation technologies for acid mine drainage: Recent trends and future perspectives - Umar Daraz; Yang Li; Iftikhar Ahmad; Rashid Iqbal; Allah Ditta (Chemosphere, 2023)

Efficacy of Different Endophytic Bacterial Strains in Enhancing Growth, Yield, and Physiological and Biochemical Attributes of Linum usitatissimum L - Khuram Shehzad Khan; Muhammad Farhan Qadir; Adeel Ahmad; Muhammad Naveed; Taqi Raza; Allah Ditta (Journal of Soil Science and Plant Nutrition, 2022)

Assessment of Pb and Ni and potential health risks associated with the consumption of vegetables grown on the roadside soils in District Swat, Khyber Pakhtunkhwa, Pakistan - Fazal Mabood; Fazal Hadi; Amin Ullah Jan; Allah Ditta; Ziaul Islam; Manzer H. Siddiqui; Hayssam M. Ali; Ayman E. L. Sabagh (Environmental Monitoring and Assessment, 2022)

Types, sources, socioeconomic impacts, and control strategies of environmental noise: a review - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Allah Ditta; Predrag Ilic; Muhammad Amin; Abdul Basit Naveed; Aadil Gulzar (Environmental Science and Pollution Research, 2022)

Genome-wide identification and analysis of the GUB_WAK_bind gene family in Gossypium hirsutum - Yingying Tang; Haodong Chen; Tingting Deng; Yan Chang; Kangtai Sun; Allah Ditta; Muhammad Kashif Riaz Khan; Kai Wang; Baohua Wang (Molecular Biology Reports, 2022)

Exploring the potential of Eocene carbonates through petrographic, geochemical, and geotechnical analyses for their utilization as aggregates for engineering structures - Abdul Rahim Asif; Ihtisham Islam; Waqas Ahmed; Muhammad Sajid; Adnan Qadir; Allah Ditta (Arabian Journal of Geosciences, 2022)

Development of Basmati lines by the introgression of three bacterial blight resistant genes through marker-assisted breeding - Allah Ditta Babar; Abha Zaka; Shahzad Amir Naveed; Niaz Ahmad; Kashif Aslam; Muhammad Asif; Umer Maqsood; Casiana M. Vera Cruz; Muhammad Arif (Euphytica, 2022)

Comparative efficacy of different biochars and traditional manures in the attenuation of cadmium toxicity in rice (Oryza sativa L.) - Abdul Majeed; Atif Muhmood; Abid Niaz; Allah Ditta; Muhammad Nawaz Rajpar (Arabian Journal of Geosciences, 2022)

Determinants and implications of environmental practices for waste management and the minimization in the construction industry: a case study of Pakistan - Ahsan Riaz Khan; Allah Ditta; Muhammad Sajid Mehmood; Zheng MaoSheng; Maryam Natalia (Environmental Science and Pollution Research, 2021)

Biochar for the Management of Nutrient Impoverished and Metal Contaminated Soils: Preparation, Applications, and Prospects - Ghulam Murtaza; Allah Ditta; Naseer Ullah; Muhammad Usman; Zeeshan Ahmed (Journal of Soil Science and Plant Nutrition, 2021)

Processed animal manure improves morpho-physiological and biochemical characteristics of Brassica napus L. under nickel and salinity stress - Muhammad Naveed; Allah Ditta; Maryum Ahmad; Adnan Mustafa; Zulfiqar Ahmad; Manuel Conde-Cid; Shermeen Tahir; Syed Atizaz Ali Shah; Muhammad Mohsin Abrar; Shah Fahad (Environmental Science and Pollution Research, 2021)

Correction to: Bacillus subtilis Y16 and biogas slurry enhanced potassium to sodium ratio and physiology of sunflower (Helianthus annuus L.) to mitigate salt stress - Samina Hamid; Iftikhar Ahmad; Muhammad Javed Akhtar; Muhammad Nadeem Iqbal; Muhammad Shakir; Muhammad Tahir; Atta Rasool; Annum Sattar; Mahreen Khalid; Allah Ditta; Bo Zhu (Environmental Science and Pollution Research, 2021)

Plant growth regulators and EDTA improve phytoremediation potential and antioxidant response of Dysphania ambrosioides (L.) Mosyakin & Clemants in a Cd-spiked soil - Amin Ullah Jan; Fazal Hadi; Abdullah Shah; Allah Ditta; Muhammad Asif Nawaz; Muhammad Tariq (Environmental Science and Pollution Research, 2021)

Bacillus subtilis Y16 and biogas slurry enhanced potassium to sodium ratio and physiology of sunflower (Helianthus annuus L.) to mitigate salt stress - Samina Hamid; Iftikhar Ahmad; Muhammad Javed Akhtar; Muhammad Nadeem Iqbal; Muhammad Shakir; Muhammad Tahir; Atta Rasool; Annum Sattar; Mahreen Khalid; Allah Ditta; Bo Zhu (Environmental Science and Pollution Research, 2021)

Alleviation of cadmium stress by silicon nanoparticles during different phenological stages of Ujala wheat variety - Sumaira Thind; Iqbal Hussain; Rizwan Rasheed; Muhammad Arslan Ashraf; Abida Perveen; Allah Ditta; Saddam Hussain; Nighat Khalil; Zahid Ullah; Qaisar Mahmood (Arabian Journal of Geosciences, 2021)

Insights into conventional and recent technologies for arsenic bioremediation: A systematic review - Sana Irshad; Zuoming Xie; Sajid Mehmood; Asad Nawaz; Allah Ditta; Qaisar Mahmood (Environmental Science and Pollution Research, 2021)

Assessment of health and ecological risks of heavy metal contamination: a case study of agricultural soils in Thall, Dir-Kohistan - Irshad Ullah; Allah Ditta; Muhammad Imtiaz; Sajid Mehmood; Muhammad Rizwan; Muhammad Shahid Rizwan; Amin Ullah Jan; Iftikhar Ahmad (Environmental Monitoring and Assessment, 2020)

Novel Biosynthesis of Copper Nanoparticles Using Zingiber and Allium sp. with Synergic Effect of Doxycycline for Anticancer and Bactericidal Activity - Atif Yaqub; Naila Malkani; Arifa Shabbir; Sarwar Allah Ditta; Fouzia Tanvir; Shaista Ali; Misbah Naz; Syed Akif Raza Kazmi; Rehan Ullah (Current Microbiology, 2020)

Geophysical and geotechnical characterization of shallow subsurface soil: a case study of University of Peshawar and surrounding areas - Ihtisham Islam; Waqas Ahmed; Mehboob Ur Rashid; Azmat Ullah Orakzai; Allah Ditta (Arabian Journal of Geosciences, 2020)

Integrated Effect of Algal Biochar and Plant Growth Promoting Rhizobacteria on Physiology and Growth of Maize Under Deficit Irrigations - Naseer Ullah; Allah Ditta; Azeem Khalid; Sajid Mehmood; Muhammad Shahid Rizwan; Muhammad Ashraf; Fathia Mubeen; Muhammad Imtiaz; Muhammad Mazhar Iqbal (Journal of Soil Science and Plant Nutrition, 2020)

Antibiotics in poultry manure and their associated health issues: a systematic review - Juma Muhammad; Sardar Khan; Jian Qiang Su; Abd El-Latif Hesham; Allah Ditta; Javed Nawab; Abid Ali (Journal of Soils and Sediments, 2020)

Response of growth, antioxidant enzymes and root exudates production towards As stress in Pteris vittata and in Astragalus sinicus colonized by arbuscular mycorrhizal fungi - Liu Yizhu; Muhammad Imtiaz; Allah Ditta; Muhammad Shahid Rizwan; Muhammad Ashraf; Sajid Mehmood; Omar Aziz; Fathia Mubeen; Muhammad Ali; Nosheen Noor Elahi; Raina Ijaz; Sha Lele; et al. (Environmental Science and Pollution Research, 2020)

Genome wide characterization, evolution and expression analysis of FBA gene family under salt stress in Gossypium species - Muhammad Shehzad; Allah Ditta; Xiaoyan Cai; Zhongli Zhou; Xingxing Wang; Yanchao Xu; Yuqing Hou; Muhammad Yasir; Majid Khan; Kunbo Wang; Fang Liu (Biologia, 2019)

Role of biochar and plant growth promoting rhizobacteria to enhance soil carbon sequestration—a review - Rubab Sarfraz; Azhar Hussain; Asma Sabir; Ibtissem Ben Fekih; Allah Ditta; Shihe Xing (Environmental Monitoring and Assessment, 2019)

Comparative Effects of Biochar, Slag and Ferrous–Mn Ore on Lead and Cadmium Immobilization in Soil - Sajid Mehmood; Muhammad Rizwan; Saqib Bashir; Allah Ditta; Omar Aziz; Li Zhe Yong; Zhihua Dai; Muhammad Akmal; Waqas Ahmed; Muhammad Adeel; Muhammad Imtiaz; Shuxin Tu (Bulletin of Environmental Contamination and Toxicology, 2018)

Effectiveness and benefit cost ratio of selected insecticides at different applicationon intervals for brinjal shoot and fruit borer, Leucinodes orbonalis (G.) management on brinjal, Solanum melongena (L.) at Sahiwal, Pakistan - Qudsia Yousafi; Muhammad Afzal; Muhammad Aslam; Allah Ditta Abid (Phytoparasitica, 2016)